Hamlet and Its Danish Double. The Historical Performance as Medium for a Utopian Monarchy : A Crooked Mirror of the Local Political Realities - Kuhlmann, Annelis (Nordic Theatre Studies, 2023)
The first Hamlet production in Danish, performed 1813 at The Royal Danish Theatre in Copenhagen, went through substantial cuts and changes in the text. The re-cycling of sets from other performances were used in the production of Hamlet and turned the reworked version of Hamlet into a negotiation of the utopian heroic vision of the Danish monarchy, despite its painful bloody conflicts of power. It is my point, that this production of Hamlet, by the dramaturgical choices made, became, what I would determine as, a plain “theatricality” of the play and with the desire for a peaceful future without conflicts. The invisibility of Shakespeare’s “utopia” was transformed into an almost theatricalized “anti-utopia” or dystopia in this production with an affinity for melodrama. How seemingly strange and paradoxical this dramaturgy was, the production of the first Danish Hamlet paved the way for a historically very long stylized form of reality in its impact on the long ninetieth century Danish theatre history. The theatrical way of thinking, as embedded in Shakespeare’s play, was adopted into a theatre mentality where dreams would echo the idea of the Royal interest and taste, leaving an impression of conform aesthetics. The dramaturgical choices from 1813 lasted until the time when Henrik Ibsen’s naturalist plays would have their opening nights at the very same Royal Danish Theatre.